2022
DOI: 10.1186/s12967-022-03372-0
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin resistance-related multi-omics differences and the establishment of machine learning models

Abstract: Objectives Platinum-based chemotherapies are currently the first-line treatment of non-small cell lung cancer. This study will improve our understanding of the causes of resistance to cisplatin, especially in lung adenocarcinoma (LUAD) and provide a reference for therapeutic decisions in clinical practice. Methods Cancer Cell Line Encyclopedia (CCLE), The Cancer Genome Atlas (TCGA) and Zhongshan hospital affiliated to Fudan University (zs-cohort) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Few studies have reported that HOXA1 regulates the radiosensitivity of cancer cells. However, it has been reported that high HOXA1 expression is correlated with cisplatin resistance of lung adenocarcinoma (34). In addition, many studies have reported that HOXA1 promoted proliferation and invasion of different cancer types (13,30,35).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported that HOXA1 regulates the radiosensitivity of cancer cells. However, it has been reported that high HOXA1 expression is correlated with cisplatin resistance of lung adenocarcinoma (34). In addition, many studies have reported that HOXA1 promoted proliferation and invasion of different cancer types (13,30,35).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation analysis between gene expression and metabolites were performed. Metabolites with p -value < 0.05 and | cor | > 0.5 were selected in this study and shown in the heat map using “ggplot2” package in R software ( Sui et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…TP53 is a classic tumor suppressor gene involved in many malignant tumors, often accompanied by advanced tumor grade and poor prognosis, with high proliferative and invasive ability and genomic instability[ 35 ]. TP53 mutation may cause resistance to platinum, fluorouracil and other chemotherapeutic drugs[ 36 , 37 ], and TP53 mutations may reduce radiotherapy sensitivity by promoting cell proliferation and metastasis[ 38 , 39 ]. This may be one of the reasons why Patient 1 progressed after 25 radiation treatments.…”
Section: Discussionmentioning
confidence: 99%